Determinant of Earnings Response Coefficient with Sales Growth as Moderating - Pramesti, I Gusti Ayu Asri; Murwaningsari, Etty (ETIKONOMI, 2025)
Research Originality: This study provides a new perspective by including the less explored sales growth as a factor that could potentially strengthen or weaken the relationship between earnings and market response. Investigating sales growth is crucial, as it enhances investor perceptions of revenue growth, a key indicator of corporate success.Research Objectives: This study analyzes the factors that affect earnings response coefficients in basic material and industrial companies listed on the Indonesia Stock Exchange in 2020–2022.Research Methods: This study uses secondary data that consisted of 76 companies with 228 observations in the basic material and industrial sectors listed on the Indonesia Stock Exchange from 2020 to 2022. This research uses multiple linear regression analysis and the data distribution is panel data.Empirical Results: The findings show that free cash flow has a positive effect on the earnings response coefficient, and systematic risk has a negative effect. Capital expenditure does not affect the earnings response coefficient. Sales growth, as moderation, can weaken systematic risk on the earnings response coefficient.Implication: This study had theoretical implications for examining the theory related to the earnings response coefficient. Practically, it provided investors with an overview of earnings quality, as shown by capital expenditure and free cash flow.JEL Classification: L6, D21, G10How to Cite:Pramesti, I. G. A. A., & Murwaningsari, E. (2025). Determinant of Earnings Response Coefficient with Sales Growth as Moderating. Etikonomi, 24(1), 233 – 246. https://doi.org/10.15408/etk.v24i1.38165.